The Effect of ESG on Firm Value and Performance During Covid-19: Moderation Role of Industry Characteristic - Dogi, Dean Charlos Padji; Lomousinea, Ian Edbert; Widuri, Retnaningtyas (International Journal of Pertapsi, 2024)
The objective of this study was to examine the correlation between Environmental, Social, and Governance (ESG), corporate value and performance, with the aim of establishing a basis for assessing ESG. An independent variable is the ESG score. The variables that will be measured are firm value and performance. Firm performance will be assessed using return on assets (ROA), while firm value will be indicated by Tobin's Q. Industrial growth, which quantifies the development of industrial aspects, will serve as a moderator to harmonise the connection between the independent and dependent variables. Analysis of data indicates that ESG factors have a detrimental effect on company value. ESG improves the performance of enterprises. Moreover, the growth of the industry does not alleviate the connection between environmental, social, and governance (ESG) factors and the value of a business. The correlation between ESG and corporate success is mitigated by the growth of the industry.